Patchouli Essential Oil and Its Derived Compounds Revealed Prebiotic-Like Effects in C57BL/6J Mice - Leong, Waikit; Huang, Guoxin; Khan, Imran; Xia, Wenrui; Li, Yucui; Liu, Yuhong; Li, Xiaoang; Han, Ruixuan; Su, Ziren; Hsiao, W. L. Wendy (Frontiers in Pharmacology, 2019)
Pogostemon cablin (PC) is a Chinese medicinal plant traditionally used for the treatment of gastrointestinal symptoms. To investigate the prebiotic effect of patchouli essential oil (PEO) and its derived compounds through the modulation of gut microbiota (GM). C57BL/6J mice were treated with the PEO and three active components of PEO, i.e. patchouli alcohol (PA), pogostone (PO) and β-patchoulene (β-PAE) for 15 consecutive days. Fecal samples and mucosa were collected for GM biomarkers studies. PEO, PA, PO, and β-PAE improve the gut epithelial barrier by altering the status of E-cadherin vs. N-cadherin expressions, and increasing the mucosal p-lysozyme and Muc 2. Moreover, the treatments also facilitate the polarization of M1 to M2 macrophage phenotypes, meanwhile, suppress the pro-inflammatory cytokines. Fecal microbial DNAs were analyzed and evaluated for GM composition by ERIC-PCR and 16S rRNA amplicon sequencing. The GM diversity was increased with the treated groups compared to the control. Further analysis showed that some known short chain fatty acids (SCFAs)-producing bacteria, e.g. Anaerostipes butyraticus, Butytivibrio fibrisolvens, Clostridium jejuense, Eubacterium uniforme, and Lactobacillus lactis were significantly enriched in the treated groups. In addition, the key SCFAs receptors, GPR 41, 43 and 109a, were significantly stimulated in the gut epithelial layer of the treated mice. By contract, the relative abundance of pathogens Sutterlla spp., Fusobacterium mortiferum, and Helicobacter spp. were distinctly reduced by the treatments with PEO and β-PAE. Our findings provide insightful information that the microbiota/host dynamic interaction may play a key role for the pharmacological activities of PEO, PA, PO, and β-PAE.